Existential risk assessment: A reply to Baum. (September 2020) - Beard, Simon; Rowe, Thomas; Fox, James
Highlights: Seth Baum's reply to our paper makes a very valuable contribution to this literature. We raise some concerns about the definitions of terms like 'existential catastrophe' and how they can be both normative and non-normative. While accepting Baum's contention that there is a trade-off between rigour and accessibility of methods, we show how the community of Existential Risk Studies could easily improve in relation to both these desiderata. Finally, we discuss the importance of context within which quantification of the likelihood of existential hazards takes place, and how this impacts on the appropriateness of different kinds of claim. Abstract: We welcome Seth Baum's reply to our paper. We broadly agree with the points Baum makes; however, the field of Existential Risk Studies remains young and undeveloped, and we think that there are many points on which further reflection is needed. We briefly discuss three: the normative aspects of terms like 'existential catastrophe, ' the opportunities for low hanging fruit in method selection and application, and the importance of context when making probability claims.